Keputusan Berbelanja Ditinjau dari Lokasi, Harga, dan Kualitas Pelayanan pada Matahari Department Store di Kota Makassar - Elyas Albar; Firmansyah Halim; Aswar Aswar (SEIKO : Journal of Management & Business, 2022)
The purpose of research to know the shopping decision to consumers Matahari Department Store in Makassar City, by a factor of location, price, and quality of service. The method used is quantitative. The population is all customers. Determination of the sample refers to the table Krejcie & Morgan, so number of respondents is 385 people. The questionnaire was measured by a Likert Model Scale, which had been tested for validity and reliability. Classical assumption test consists of normality test, multicollinearity, and heteroscedasticity test. Next, multiple linear regression test to the hypothesis. Results of the study simultaneously and partial show that the variable of prices ( X1 ), location ( X2 ), quality of the services ( X3 ) have a positive impact significant of the purchasing decisions (Y) in Matahari Department Store in Makassar City. Simultaneously the correlation coefficient value of 0.421 or 42.1% indicates that the price, location, and service quality variables together have an influence of 42.1% on the purchasing decision variable, while the remaining 57.9% is influenced by other factors that not the focus of this study. Partially, the research variable has an effect of 0.195 or 19.5%, location has an effect of 0.153 or 15.3%, and service quality has an effect of 0.073 or 7.3% on purchasing decisions consumers Matahari Department Store in Makassar City.